2022
DOI: 10.14202/vetworld.2022.782-788
|View full text |Cite
|
Sign up to set email alerts
|

Association of pleomorphic adenoma gene 1 with body weight and measurement of Bali cattle (Bos javanicus)

Abstract: Background and Aim: Pleomorphic adenoma gene 1 (PLAG1) encodes a multifunctional transcription factor that controls many genes and pathways and is associated with cattle body weight and measurements. This study aimed to evaluate the association between PLAG1 polymorphisms with body weight and measurements in Bali cattle. Materials and Methods: A total of 87 Bali cattle, consisting of 48 bulls and 39 heifers at the Breeding Center for Bali Cattle, were used as the population in this study. Cattle were 2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…CC, TC, and TT genotypes (Figure 1). Similar results were also found in Qinchuan cattle and Bali cattle [10,13]. In term of 19 bp indel in unproductive Kebumen PO cattle used in this study were only two genotypes found, i.e.…”
Section: Relationship Of Plag1 Gene Polymorphisms and Body Measuremen...supporting
confidence: 88%
See 2 more Smart Citations
“…CC, TC, and TT genotypes (Figure 1). Similar results were also found in Qinchuan cattle and Bali cattle [10,13]. In term of 19 bp indel in unproductive Kebumen PO cattle used in this study were only two genotypes found, i.e.…”
Section: Relationship Of Plag1 Gene Polymorphisms and Body Measuremen...supporting
confidence: 88%
“…Non-significant effect in this study may be due to different population and cattle breeds used compared to previous reports. As reported in previous study, 19 bp indel mutation is located on intron 3 of the PLAG1 [13]. It is known that mutations in introns also affect protein expression by influencing the mRNA splicing process in these genes [18].…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The g.48308 C>T SNP is a polymorphism located in 3' untranslated region (3'UTR) and the size of PCR products to identify this SNP is in accordance to previous study reported by Zhong et al [9]. Additionally, g.45233 T>C SNP located in exon 4 of PLAG1 was successfully amplified and the PCR product size was similar with Cahyadi et al [8]. Specific DNA bands is produced only when all reaction components working simultaneously and in optimum condition [15].…”
Section: Amplification Of the Plag1 Fragmentssupporting
confidence: 88%
“…These three genes have homolog structure but different functions [7]. Recently, Cahyadi et al [8] identified a single nucleotide polymorphism (SNP) of the PLAG1 and its significant association with body length of Bali cattle. The same SNP, g.48308 C>T SNP, is also associated with body height and chest girth of five cattle breeds in China [9].…”
Section: Introductionmentioning
confidence: 99%